General lipid biomarker from the NGaoundaba peat deposit (Tropical Africa) covering the Holocene - Schaaff, Valentine; Grossi, Vincent; Makou, Matthew; Garcin, Yannick; Deschamps, Pierre; Hamelin, Bruno; Kiahtipes, Christopher Albert; Sebag, David; Ngounou Ngatcha, Benjamin; Ménot, Guillemette (PANGAEA, 2025)
This dataset includes lipid biomarker data from a peat sequence (named NGBA19) collected at the NGaoundaba peat deposit in 2019. The NGaoundaba peat deposit is located in North East Cameroon (N 7.135°, E 13.690°, 1175 m a.s.l). The 6-meter core was collected using a Russian peat corer. The core was subsampled at 2.5-cm intervals. Analyses were performed on 73 samples. Measurements were performed between 2020 and 2024 at the LGL-TPE (ENS de Lyon and University Claude Bernard Lyon 1). The NGBA19 core covers the last 10 ka (detail on the datation method and results are given in Schaaff et al. (2023, doi:10.1016/j.orggeochem.2023.104589). This dataset is associated to a publication: Sensitivity to climate and vegetation dynamics of a peatland record from Central Cameroon during the African Humid Period (QSR). The publication details the full method used to obtain the data. The study focus on paleoclimatic and paleoenvironmental reconstructions particularly during and after the African Humid Period. This file contains long-chain n-alkane data (n-C29, n-C31, n-C33 alkanes): relative abundance and concentration for each compounds and ratios (carbon preference index - CPI, average chain length - ACL and Paq). These data were collected using GC-MS (compound identification and quantification). The file also includes a ratio based on brGDGTs: the methylation of branched tetraethers (MBT'5Me) ratio and brGDGT-based temperature reconstructions using 4 different calibrations presented in the associated article.
Keywords: African Humid Period; alkanes; Biomarker; GDGT; pollen analysis; Tropical peatlands